The viability of conferment of quasi-judicial power to land administrator as a mechanism of protection against fraudulent transfer: with particular reference to western Australia and Singapore / Azmur Amira Azhar …[et al.] - Azhar, Azmur Amira; Hassan Basri, Hanorizatty; Mohmad Noor, Nurain Amalina Fatanah; Maswari, Nur Rafi'uddin (2014)
This research paper analyses the viability of conferring quasi-judicial power to the Land Administrator with regards to transfer transaction. This research paper investigates and examines on different types of commission of frauds and whether the conferment of the quasi-judicial power would bring any beneficial effect in preventing further fraudulent transfer transactions. This research also compares Malaysian's current transfer registration process with those from other countries, such as Singapore and West Australia, especially on their security to prevent any risks of fraud. This research is a fully library based, as collections of data and relevant information are extracted from scholarly journals, books and articles. At the conclusion, we will provide the recommendations to implement the conferment of quasi-judicial power to Land Administrator.